Influence of Cylindrical Shield Dimensions on Shielding Effectiveness - O. D. Kanafyev; A. V. Trukhanov; T. I. Zubar; S. S. Grabchikov; M. I. Panasiuk; A. N. Kotelnikova; V. A. Fedkin; V. M. Fedosyuk (Приборы и методы измерений)
Study of dimensional parametersʼ influence on shielding properties of cylindrical shields will allow to optimise the fusion process, as well as to reduce production costs by reducing the material used. The purpose of this work was to compare results of theoretical calculation of shielding effectiveness of an infinite cylindrical shield with the data obtained in real conditions.A cylindrical Ni-Fe shield was synthesised by electrochemical deposition with length of 32 cm, diameter of 4.5 cm and shielding thickness of ≈ 100 µm. The cylinder length was then reduced from 32 cm to 6 cm in 4 cm increments and for each cylinder length shielding effectiveness was measured using three-coordinate Helmholtz field-forming system.The measurement results show that the calculation of shielding effectiveness of infinite cylindrical shield is valid for cylinder lengths l ≥ 18–20 cm. Shielding effectiveness is markedly reduced at values of l ˂ 15 cm.Analysis of data obtained allowed to conclude that it is necessary to determine the correction factor when calculating a cylindrical screen shielding efficiency